Willingness to establish private forest plantations among households in Oyo State Nigeria (2019)
This study investigates the willingness of the respondents to establish private forest plantations (PFPs) in Oyo State, Nigeria. Two purposively selected and two randomly selected local government areas were used. One hundred and sixty household heads randomly selected were interviewed using the interview schedule and the data analysis was carried out using both descriptive (frequencies, percentages, mean) and inferential (Chi-Square and PPMC) statistics with 0.05. The majority of the respondents were male (89.2%), within 41–50 years (43.9%) and 92.8% were married. About 85.6% have knowledge of private ownership and 91.4% had knowledge on forest plantation establishment. Respondents’ attitude towards PFPs (78.4%) was favourable. A large percentage (96.4%) agreed that involvement in PFPs serves as income generating activity, whereas 58.3% identified government policy on forestry and land tenure system as major constraints to establishing PFPs. There were significant relationships between age (x2 =236.256), educational qualification (x2 = 35.283), primary occupation (x2 = 62.944) private ownership (r = 0.424), knowledge on forest plantation (r = 0.451), perception (r = 0.230), perceived benefits (r = 0.180), perceived constraints (r = −0.181) and willingness to establish PFPs. Respondents possessed high knowledge and favourable attitude towards PFPs despite the perceived constraints. The state, in collaboration with the Forestry Research Institute of Nigeria (FRIN), should initiate programmes to emphasise benefits of PFPs in order to encourage more participation and government policy on land use decree should be reviewed to promote participation in forest plantation establishment.